Citizen aid: grassroots interventions in development and humanitarianism. Issue 10 (3rd October 2019) - Fechter, Anne-Meike; Schwittay, Anke
Abstract: The introduction to this collection brings together, under the umbrella terms of citizen aid and grassroots humanitarianism, interdisciplinary research on small-scale, privately funded forms of aid and development. It notes the steady rise of these activities, including in the Global South as well as North, such as in the context of the recent European refugee crisis. It considers their position vis-à-vis more institutionalised forms of aid; methodological approaches and their challenges; and asks what political dimensions these initiatives may have. It outlines key themes arising from the contributions to the collection, including historical perspectives on 'demotic humanitarianism', questions of legitimacy and their apparent lack of professionalisation, motivations of their founders, the role of personal connections, as well as the importance of digital media for brokerage and fundraising. Being mindful of its critiques and implicit power imbalances, it suggests that citizen aid deserves more systematic academic attention.